2011
DOI: 10.1590/s0102-33062011000200009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito alelopático e toxicidade frente à Artemia salina Leach dos extatos do fruto de Euterpe edulis Martius

Abstract: ABSTRACT(Allelopathic eff ects and toxicity against Artemia salina Leach of extracts of the fruit of Euterpe edulis Martius). Allelopathy is a process involving secondary metabolites produced by plants that infl uence growth and development of agricultural systems. Because of the toxicity of synthetic herbicides to the environment and human health, there has been increased interest in exploiting allelopathy as an alternative for weed control. Th is study evaluated the eff ect of extracts of Euterpe edulis Mart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
5
0
4
Order By: Relevance
“…Allelopathic substances are not commonly described in palms, although Lima et al (2011) reported an allelopathic effect of E. edulis fruits on Lactuca (Mengardo, unpublished data). Here, we only checked a plant-to-plant approach (Inderjit et al 2008), which revealed no indirect effect of the invasive on the native species.…”
Section: Discussionmentioning
confidence: 99%
“…Allelopathic substances are not commonly described in palms, although Lima et al (2011) reported an allelopathic effect of E. edulis fruits on Lactuca (Mengardo, unpublished data). Here, we only checked a plant-to-plant approach (Inderjit et al 2008), which revealed no indirect effect of the invasive on the native species.…”
Section: Discussionmentioning
confidence: 99%
“…A utilização de extratos vegetais é uma alternativa ao uso de herbicidas sintéticos para o controle de plantas invasoras. Dentre as vantagens são citadas: menor efeito residual no ambiente e menor risco a saúde humana (LIMA et al, 2011).…”
Section: Resultsunclassified
“…A Artemia sp é utilizada desde a década de 50 para inúmeros estudos de ecotoxicidade e na avaliação de produtos como pesticidas, derivados do petroquímicos e dispersantes, metais pesados, derivados carcinogênicos além de metabólitos de microorganismos. Como os produtos naturais estão sujeitos aos mesmos problemas tóxicos dos pesticidas, pesquisas alelopáticas e de fitotoxicidade devem ser conduzidas paralelamente a estudos de ecotoxicidade e toxicidade para humanos, uma vez que substâncias desenvolvidas e utilizadas como agrotóxicos podem causam danos ambientais e a saúde humana (Lima et al, 2011 Estudos com a espécie Celtis iguanaea devem ser realizados em campo sobre o efeito em espécies daninhas e com a finalidade de estabelecer a ação fitotóxica destes compostos no ambiente.…”
Section: Discussionunclassified